Lipomatous mixed tumor of the skin with predominance of stromal fat - P S Jayalakshmy; Rohini Sebastian; M Feroze; Lovely Jose (Wolters Kluwer Medknow Publications, 2016)
A rare variant of cutaneous chondroid syringoma, with epithelial differentiation composed of apocrine, follicular, and sebaceous components and showing the presence of predominantly lipomatous stroma, is being reported in a 54-year-old female.